Resilience among Malaysian adolescent cancer patients and their caregivers: a review - Chaudhry, Zainab; Abu Talib, Mansor; Awang, Hamidin; Ahmad, Sa'odah (Elite Scientific Forum, 2016)
Cancer is one of the diseases which have severe psychological and physiological implications in the affected patients, and it gets an even uglier form in case of childhood cancer that engulfs the entire household. The devastating nature of the childhood cancer causes a wave like effect which goes from adolescent to the parents/caregivers/family, making it a family disease. Along with the distressing effects and side effects of cancer the adolescents are constantly grappled with the developmental issues, whereas, family/caregivers struggle with a unique adaptation and evolution, due to the challenges posed by the disease. The current paper is a literature review of resilience among adolescent cancer patients (ACPs) and their caregivers, in Malaysian backdrop. It offers an insight into the gap in the current knowledge and highlights the need of an analysis of the concept of resilience among the targeted population in accordance with specific cultural considerations. The review primarily based upon studies targeting adolescents with the disease and their caregivers, their stressors; and processes of adjustment and coping while highlighting the cultural and religious aspect. It established the fact that in Malaysia, ACPs have hardly been studied unlike their caregivers. It's essential to consider the optimistic concepts such as resilience as a foundation stone for those who are struggling with health challenges, directly or indirectly, especially in Asian societies, while focusing on their cultures, religion and spirituality. It's the responsibility of the clinicians, researchers and health care providers to undertake the research and recommend new ways of living for the patients and those related.